2018
DOI: 10.1016/j.radonc.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy utilization in developing countries: An IAEA study

Abstract: The optimal RTU rate in middle-income countries did not differ significantly from that previously found in high-income countries. The actual RTU rates were consistently lower than the optimal, in particular in countries with limited resources and a large population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Requirements for radiotherapy are considered much higher in low-income countries due to late stage presentation and thus, more commonly used palliative therapy concepts including radiotherapy [39]. A recent IAEA study showed a median unmet need for radiation in developing countries of 47% [40]. Having only one single Cobalt-60 machine in use for the whole of Ethiopia, waiting time will continue to increase due to the increasing patient load and prolonged radiation-times resulting from the decreasing efficacy of the machine.…”
Section: Discussionmentioning
confidence: 99%
“…Requirements for radiotherapy are considered much higher in low-income countries due to late stage presentation and thus, more commonly used palliative therapy concepts including radiotherapy [39]. A recent IAEA study showed a median unmet need for radiation in developing countries of 47% [40]. Having only one single Cobalt-60 machine in use for the whole of Ethiopia, waiting time will continue to increase due to the increasing patient load and prolonged radiation-times resulting from the decreasing efficacy of the machine.…”
Section: Discussionmentioning
confidence: 99%
“…Retreatment is less common in lowand middle-income countries. Retreatment ranged from 7 to 24% in a study of middle-income countries by the International Atomic Energy Agency [12].…”
Section: Demand For Palliative Radiotherapymentioning
confidence: 99%
“… 8 , 9 , 10 Even today, the available RT infrastructure and complementary human resources is insufficient to meet the growing RT demands, especially in the low- and middle-income economies. 11 , 12 , 13 , 14 , 15 , 16 , 17 The situation is likely to worsen as most countries may find it difficult to designate adequate finances for establishing new RT infrastructure in the post COVID-19 era.…”
Section: Introductionmentioning
confidence: 99%